Community perceptions surrounding Lisbon's first mobile drug consumption room - Hannah Taylor; Ângela Leite; Diana Gautier; Patrícia Nunes; Joana Pires; Adriana Curado (Elsevier, 2022)
Portugal's first Mobile Drug Consumption Room (MDCR) has been operating for over three years in two Lisbon neighborhoods. This qualitative study first creates a baseline understanding of community perceptions concerning the acceptability of and expectations surrounding drug consumption rooms in the communities of intervention. Then, at least six months after the initial interviews, it determines how these perceptions changed and what changes participants perceive in the neighborhoods. Findings highlight widespread acceptance of the MDCR among participants. One of the participants' priorities related to the MDCR was to lessen the visibility of public consumption, a change some participants perceived in the neighborhood. While in the first round of data collection participants primarily conceptualized the MDCR as a service for People Who Use Drugs (PWUD), in the follow-up round, they reported changes in the community.